2017
DOI: 10.1186/s12872-017-0493-6
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention strategies after an acute ST-segment elevation myocardial infarction in the AMI code era: beyond myocardial mechanical reperfusion

Abstract: BackgroundThe AMI code is a regional network enhancing a rapid and widespread access to reperfusion therapy (giving priority to primary angioplasty) in patients with acute ST-segment elevation myocardial infarction (STEMI). We aimed to assess the long-term control of conventional cardiovascular risk factors after a STEMI among patients included in the AMI code registry.Design and methodsFour hundred and fifty-four patients were prospectively included between June-2009 and April-2013. Clinical characteristics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
2
9
1
Order By: Relevance
“…With regard to socio-demographic characteristics, the proportion of men and women in our study is not balanced (28.7% of women) and it is similar to previous studies. [13,14,24,25] We found that women were older, had greater comorbidity at baseline and received more comedications after the study event than men, probably because they were older when had the rst ACS, as described in a similar cohort by Ribas et al [25] In agreement with similar studies, we found a higher prevalence of comorbidities in women, [26][27][28] while men had a higher prevalence of peripheral artery disease, [29] possibly related with the higher frequency of smoking habit.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to socio-demographic characteristics, the proportion of men and women in our study is not balanced (28.7% of women) and it is similar to previous studies. [13,14,24,25] We found that women were older, had greater comorbidity at baseline and received more comedications after the study event than men, probably because they were older when had the rst ACS, as described in a similar cohort by Ribas et al [25] In agreement with similar studies, we found a higher prevalence of comorbidities in women, [26][27][28] while men had a higher prevalence of peripheral artery disease, [29] possibly related with the higher frequency of smoking habit.…”
Section: Discussionsupporting
confidence: 90%
“…The literature stated that survivors of STEMI remained at high long-term risk of recurrent ischaemic cardiovascular events 20 21 and mortality, and demonstrated the effectiveness of patient education in decreasing the risk with changing the key lifestyle habits in particular smoking cessation 22 and control of the high density lipoproteinlevel. 21 The literature has also highlighted that secondary prevention strategies after a STEMI episode are still far from being optimal 23 and also denoted substantial problem of guidance documents for clinicians. 24 These results potentially counterbalance the prognostic benefits of the reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The direct cost of hospitalization in the United States is at least $450 billion and the loss of productive life years is also tremendous [2]. Prompt restoration of blood flow is crucial to salvage ischemic myocardium [3]. Reperfusion strategies such as primary percutaneous coronary intervention (PCI) and thrombolysis have shown to reduce mortality and infarct size and improve left ventricular function; however, reperfusion itself may result in adverse events [4].…”
Section: Introductionmentioning
confidence: 99%